Possible association between the integrity of cerebellar pathways and neurocognitive performance in children with posterior fossa tumors. Issue 9 (11th July 2020) - Liguoro, Ilaria; Passone, Eva; Zilli, Tiziana; Maieron, Marta; De Colle, Maria Cristina; Skrap, Miran; Dolcemascolo, Valentina; Sommariva, Giulia; Cogo, Paola; Tomasino, Barbara
Abstract: Background: Cerebellar tumor survivors often exhibit neuropsychological deficits that could be related to alterations in cerebro‐cerebellar networks. This is a pilot study designed to understand if diffusion tensor imaging (DTI)‐based tractography is able to identify possible correlations between cerebellar white matter structure and cognitive outcome in children on long‐term follow‐up for posterior fossa (PF) tumors who were thoroughly assessed for neuropsychological functioning. Methods: DTI‐based tractography was performed in pediatric patients with PF tumors. Fractional anisotropy (FA) and volumetric measurements of spinocerebellar, dentorubrothalamocortical and corticopontocerebellar tracts were analyzed. Cognitive and neuropsychological functioning was assessed by the Wechsler Intelligence Scale for Children–IV Edition (WISC‐IV) and the Developmental Neuropsychological Assessment (NEPSY II). The associations between Full‐Scale Intelligence Quotient (FSIQ), NEPSY‐II scores, and fiber tracts were tested by the Spearman rank correlation coefficient. Results: Seven patients (median age at diagnosis five years, range, 3‐13) treated for medulloblastoma (2/7; 29%) and pilocytic astrocytoma (5/7; 71%) were retrospectively evaluated. All children had complete surgery. The median FSIQ was 84 (range, 67‐93). Patients presented with several deficits on many NEPSY‐II tasks; in particular, memory was impaired in nearly half of them. FSIQ and neurocognitive tasks significantly correlated with specific corticopontocerebellar tracts. Conclusion: Children on follow‐up for PF tumor showed scattered cognitive impairments, including deficits in long‐term and immediate memory. Tractography allowed us to describe a possible association between the integrity of cerebellar pathways and neurocognitive performance, suggesting that the myelinization of these fibers may represent an indicator for the development of long‐term cognitive sequelae.